Desarrollo de indicadores de sostenibilidad ambiental en el sector Santa Ana del Pedregal, cantón Mejía, provincia de Pichincha, periodo de abril- agosto 2022. (Diagnostico). - Andrango Ledesma, Karla María (2022)
This research project is aimed at the development of environmental sustainability indicators in the Santa Ana of the Pedregal, canton of Mejía, province of Pichincha, through the characterization of the study area. With the application of the QGIS software tool and under the municipal GAD ordinance of Mejía, through the selection of environmental sustainability indicators present in the study area, it was possible to analyze the different indicators present in the area, which contribute to the community in caring for the environment. Obtaining information from the place to analyze the sustainability indicators, through a descriptive, inductive, deductive, bibliographic and analytical methodology; in relation to the activities carried out in the sector such as agriculture, livestock and tourism, determining the social, economic and productive performance of the place through the qualitative and quantitative modality in systems in constant degradation. Supported by the QGIS tool, the study area was characterized to determine the current socio-environmental situation. With the help of the surveys and the data obtained, it was possible to identify the way of thinking and the level of knowledge about the indicators of environmental sustainability to achieve their selection. Within the study area there is no structured environmental development plan, so an analysis was carried out based on the proposed indicators, these have an established goal to be met, efficient activities and strategies that will be basic tools for compliance and execution within of the sector. In order to mitigate the negative impacts within Santa Ana of the Pedregal, there are sufficient resources available to continue harming the environment directly and indirectly.